2011
DOI: 10.1530/rep-11-0229
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different levels of short-term feed intake on folliculogenesis and follicular fluid and plasma concentrations of lactate dehydrogenase, glucose, and hormones in Hu sheep during the luteal phase

Abstract: This study investigated the effects of short-term food restriction or supplementation on folliculogenesis and plasma and intrafollicular metabolite and hormone concentrations. Ewes were randomly assigned to three groups: the control group received a maintenance diet (M) while the supplemented group and restricted group received 1.5!M and 0.5!M respectively on days 6-12 of their estrous cycle. Estrus was synchronized by intravaginal progestogen sponges for 12 days. On days 7-12, blood samples were taken. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
39
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 51 publications
(92 reference statements)
7
39
0
2
Order By: Relevance
“…Only glucose levels were greater in large follicles compared with small follicles, with the levels of acetate, lactate, hypoxanthine, inositol, trimethylamine and the amino acids alanine, leucine, lysine, methionine and phenylalanine being lower. The finding that glucose concentration increased as follicular diameter increased is consistent with analyses of sheep (Ying et al 2011), cattle (Leroy et al 2004) and buffalo (Nandi et al 2008) FF, but contrary to findings in camels (Ali et al 2008) and horses (Collins et al 1997, Gérard et al 2002. Furthermore, Leroy et al (2004) also observed a concomitant reduction in lactate levels as follicle size increased.…”
Section: Discussionsupporting
confidence: 82%
“…Only glucose levels were greater in large follicles compared with small follicles, with the levels of acetate, lactate, hypoxanthine, inositol, trimethylamine and the amino acids alanine, leucine, lysine, methionine and phenylalanine being lower. The finding that glucose concentration increased as follicular diameter increased is consistent with analyses of sheep (Ying et al 2011), cattle (Leroy et al 2004) and buffalo (Nandi et al 2008) FF, but contrary to findings in camels (Ali et al 2008) and horses (Collins et al 1997, Gérard et al 2002. Furthermore, Leroy et al (2004) also observed a concomitant reduction in lactate levels as follicle size increased.…”
Section: Discussionsupporting
confidence: 82%
“…Thus, the measurement of LDH activity in follicular fluid is important as a potential index of early follicular degeneration. 29 LDH activity was found to reduce in follicular fluid as follicular size increased. 30,44 LDH levels increased in serum of Rahmani and Ossimi ewes, indicating the increase in tissue destruction and explained that large numbers of follicles grow were atretic, so ovulation rate declined in these two breeds; restricted Barki ewes had low LDH, so no change in their ovulation rate was observed.…”
Section: Cholesterolmentioning
confidence: 92%
“…Similarly, the concentration of serum insulin was lower in restricted ewes than in those fed ad libitum. 34 Moreover, ewes restricted by 30% for 35 days had low insulin, 35 while Hu ewes fed a 0.5-maintenance diet had slightly lower insulin levels compared to controls, 29 and concentrations of plasma insulin concentrations were lower in low-body condition than in high-body condition ewes during mid-pregnancy. 36 Overall, there were no main effects on insulin concentrations in ewes that were 50% restricted for 27 days, although the insulin levels were lower than in controls.…”
Section: Metabolic Responses Insulinmentioning
confidence: 95%
See 2 more Smart Citations